Common applications of next-generation sequencing technologies in genomic research - Lee, Chien-Yueh; Chiu, Yu-Chiao; Wang, Liang-Bo; Kuo, Yu-Lun; Chuang, Eric Y.; Lai, Liang-Chuan; Tsai, Mong-Hsun (Translational Cancer Research; Vol 2, No 1 (February 05, 2013): Translational Cancer Research, 2013)
Next-generation sequencing (NGS) technologies have progressive advantages in terms of cost-effectiveness, unprecedented sequencing speed, high resolution and accuracy in genomic analyses. To date, these high-throughput sequencing technologies have been comprehensively applied in a variety of ways, such as whole genome sequencing, target sequencing, gene expression profiling, chromatin immunoprecipitation sequencing, and small RNA sequencing, to accelerate biological and biomedical research. However, the massive amount of data generated by NGS represents a great challenge. This article discusses the available applications of NGS technologies, presents guidelines for data processing pipelines, and makes suggestions for selecting suitable tools in genomics, transcriptomics and small RNA research.